Spiritual needs experienced by the patient's family caregiver under Oncology palliative care - Renata Carla Nencetti Pereira Rocha; Eliane Ramos Pereira; Rose Mary Costa Rosa Andrade Silva; Angelica Yolanda Bueno Bejarano Vale de Medeiros; Sueli Maria Refrande; Neusa Aparecida Refrande
ABSTRACT Objective: To understand the spiritual needs of the patients' family caregiver under Oncology palliative care. Method: A descriptive, qualitative study with 20 family caregivers of patients hospitalized in an Oncology palliative unit. The data were collected through a phenomenological interview, and analyzed by the method of Amadeo Giorgi supported in the Merleau-Ponty's Phenomenology of Perception. Results: The categories were unveiled: "Spirituality as a foundation for life"; "Spiritual needs sublimated by the family caregiver"; and "Care expected by the nurse". Conclusion: Family caregivers appropriate spirituality as a coping strategy and meeting the purpose and meaning of the moment experienced. It is profitable for the nurse to contemplate the spiritual needs of the caregiver in order to provide a guided assistance in the humanization of care and comprehensive care. Therefore, there is a need for new studies that address this dimension to the family caregiver in the field of Oncology, since this care is incipient by the nurse.